Penerapan Konsep Outer Space Garden pada Perancangan Interior “Viola Florist Centre di Surabaya - Ratnamaya Wijayanti Darmawan (Intra, 2014)
“Viola Florist Centre” is an interior design which was designed to produce a one-stop-shopping florist. This interior design was designed in to accommodate various facilities such as gallery looking florist, flower arranging workshop, flower cafe, wrapping area, souvenir and gift shop. The application of an open plan Outer Space Garden concept was chosen in order to combine all of the facilities. “Viola Florist Centre” is a new place where customers can enjoy the beauty of the flowers which was displayed hanging and attached in the branch of a tree. The design of florist centre in Surabaya is believed to grow the potential flower marketing in the area.